THE NORMAL BIRTH CENTER (CPN): ITS IMPORTANCE IN THE LIVES OF PREGNANT WOMEN, PARTURIENT WOMEN, PUERPERAL WOMEN AND LACTATING WOMEN - Nascimento , Maria Eduarda Bezerra do (2024)
The objective of this article is to identify Brazilian science and its benefits in supporting live birth services. It is an integrated review process carried out through electronic databases and journal portals ( CAPES Journals, SCIELO Electronic Library and Google Scholar). Articles were selected through an online search and seven articles that met the inclusion criteria were selected. It appears that the published literature seeks to identify and describe the results achieved through ANC support for mothers and babies, in addition to satisfaction with these services. It was found that ANCs provide quality care to the mother, child and the entire family, reducing labor, medication, unnecessary interventions and complications during childbirth and providing comfort, safety and well-being to women pregnant women and babies. We care for newborns with humanized, quality care provided by professionals, especially nurses. Furthermore, when ANC was implemented, cesarean section rates were reduced and the women assisted were more satisfied with their work, as they were able to give birth independently, in addition to the support they received from family and nurses throughout the period. of childbirth. Therefore, in addition to supporting and bringing security to women, nurses become the main experts in supporting women who give birth and providing quality care.